(untitled) (Comprehensive Journal of Science, 2025)
§ The main objective of this study is to identify the availability of traffic safety equipment, as stipulated in the proposed traffic safety equipment guide, and its correlation with traffic accidents. This study was conducted in three stages: The first stage focused on collecting data related to the coastal road passing by the city of Janzour and the ring road that runs through it to survey the availability of traffic safety equipment on them. The second stage involved studying traffic accident data in this area during the period 2015-2018, as a preliminary study to determine the broad outlines of the study. The third stage involved designing a questionnaire to identify the most important factors resulting from traffic equipment that cause traffic accidents. § This study concluded the following: § • There is a 94% deficiency in the provision of traffic signals (warning, regulatory, and informational) in most sections of the coastal road in Janzour, based on the provisions of the proposed traffic safety equipment guide. § • Through analysis of the field survey of the reality of all signs for the ring road sections in the study area, it was found that there is a deficiency representing 96% in the provision of traffic signs (warning, regulatory, informational) in most sections, based on what is stated in the proposed traffic safety equipment manual. § • The most important factors resulting from the road that cause traffic accidents are the poor condition of the road surface in first place, followed by the lack of traffic safety equipment on the road in second place. § • This research shows that there is a lack of road equipment, which has contributed significantly to an increase in the number of accidents and the resulting increase in the number of deaths and injuries, as the primary purpose for which the sign was put in place is to